MUDANÇAS CLIMÁTICAS E SEUS EFEITOS NA DISTRIBUIÇÃO POTENCIAL DO CEDRO ROSA, CEDRELA FISSILIS VELL., NA BACIA DO PRATA. - CAMPOS, Larissa Tamires Boeng; BATISTA-SILVA, Valéria Flávia; MAYER, Milena Helen; BAILLY, Dayani; SILVA, Ana Francisca Gomes; MELO, Rejane Guimarães (ANAIS DO ENIC, 2022)
-